The Role of Social Media in Students’ Social Perception and Interaction: Implications for Learning and Education - Purnama, Yulian; Asdlori, Asdlori (PT. LITERASI SAINS NUSANTARA, 2023)
In today's digital age, the role of social media in education has become a subject of increasing attention. Social media, such as Facebook, Instagram and Twitter, have changed students' social interaction patterns, influenced perceptions of self and others, and have significant psychological impacts. This research discusses the role of social media in shaping students' perceptions and social interactions and its implications in learning and education. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that social media has brought about changes in the way students interact. They not only communicate in person but also through online platforms, creating new dynamics in social relationships. Students' exposure to social media content can affect their self-image and social norms. In addition, social media use can also result in social pressure and psychological impact on students. The implication of the role of social media is the need for social media literacy education, wise use of social media in learning, and necessary psychological support for students. Parents also need to be involved in their children's social media literacy education. With cooperation between educational institutions, social-media platforms, and parents, a safe educational environment that supports students' social, intellectual, and emotional development can be created.